(3HOGFd GdMHS GdGMJjGWi (B: s (3OQGSI ebGQfI (B/ s - (3CSGeI YHOGdgGOi YeQ Ydis; (3MSfjf YHjOs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2020)
(3dG Tc Cf GdMHS GdEMJjGWi ef CNWQ GdELQGAGJ GdJi JJNP VO GdeJge h CTOgG bShI h jdMb HGdeJge CVQGQkG LSjeI JeJO deMjWg GdCSQi h fTGWg Gdegfi QZe Cfg eG RGd bjO GdeMGceI(B: (3dPG cGf ef GdVQhQi Cf JSJYjf GdJTQjYGJ GdeNJdaI HHYV GdJOGHjQ GdHOjdI ddMHS GdEMJjGWi jecf ef NdGd JMbjb PGJ GdCZQGV GdJi jQei Edi JMbjbgG GdMHS GdEMJjGWi (B: (3h dcf Ohf SdH dMQjI GdeJge OGNd GdSLhf(B. (3h bO JfGhdfG ef NdGd gPG GdHMK GdJOGHjQ GdHOjdI ddMHS GdEMJjGWi(B: (3MjK NUUfG GdHGH GdChd dEdbGA GdVhA Ydi GdCMcGe GdYGeI dHOGFd GdMHS GdEMJjGWi GdhGQOI HGdbGfhf (B145 (3dSfI (B2006: (3MjK CbQ GdeTQY GdeUQi dChd eQI HOGFd ddMHS GdEMJjGWi ai GdeGOI (B201 (3ef bGfhf GdELQGAGJ GdLfGFjI(B: (3Ke JfGhdfG ai GdHGH GdKGfi cGaI GdHOGFd GdCNQi ai eNJdaI GdJTQjYGJ h ChVMfG eRGjG Jdc GdHOGFd ai GdMO ef GdBKGQ GdSdHjI GdeJQJHI Ydi GdMHS GdEMJjGWis
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFi, (B2020s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B274-285s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdbGfhf GdLfGFjs; (3GdMHS GdGMJjGWis; (3GdfjGHI GdYGeIs; (3HOGFd GdMHS GdGMJjGWis; (3GdGUd aj GdeJge GdHQGAIs; (3NUe eOI GdMHS GdGMJjGWi ef GdYbhHIs; (3bGVj GdJMbjbs; (3LQGFe GdLfGjGJs; (3LQGFe GdLfMs; (3GdGaQGL GdeDbJs; (3GdJOGHjQ GdHOjdIs; (3GdeQGbHI GdbVGFjIs; (3GdeQGbHI GdGdcJQhfjIs; (3GdcaGdI GdeGdjIs; (3GdefY ef GdJUQas; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs